New World Meteorological Organization Certified Megaflash Lightning Extremes for Flash Distance (709 km) and Duration (16.73 s) Recorded From Space. Issue 16 (19th August 2020) - Peterson, Michael J.; Lang, Timothy J.; Bruning, Eric C.; Albrecht, Rachel; Blakeslee, Richard J.; Lyons, Walter A.; Pédeboy, Stéphane; Rison, William; Zhang, Yijun; Brunet, Manola; Cerveny, Randall S.
Abstract: Identification and validation of atmospheric extremes are essential to monitoring climate change, to addressing engineering and safety concerns, and to promoting technological advancement. An international World Meteorological Organization evaluation committee has critically adjudicated and recommended acceptance of two lightning megaflash events (horizontal mesoscale lightning discharges of >100 km in length) as new global extremes using analysis of Geostationary Lightning Mapper data. The world's greatest extent for an individual lightning flash is a single flash that covered a horizontal distance of 709 ± 8 km (441 ± 5 mi) across parts of southern Brazil on 31 October 2018. The greatest duration for a single lightning flash is 16.730 ± 0.002 s from a flash that developed continuously over northern Argentina on 4 March 2019. Plain Language Summary: Analysis of new satellite data has identified lightning extremes for horizontal distance (709 km) and greatest duration (16.730 s). Key Points: Analysis of new satellite data identifies far‐larger lightning flashes (termed "megaflashes"; flashes > 100 km) than previously detected Two megaflash events are identified from space that exceed global lightning extremes (horizontal length, duration) by a factor of two The new megaflash extremes: horizontal distance is 709 km on 31 October 2018 (Brazil); duration is 16.730 s on 4 March 2019 (Argentina)